AN EFL TEACHER'S PERCEPTION OF IMPLEMENTING PROJECT-BASED LEARNING FOR SEVENTH GRADE STUDENT'S AT SMP NEGERI 29 PONTIANAK AND SMP NEGERI 3 BATU AMPAR - Sari, Lili Nur Indah; Sood, Muhammad; Yassin, Muhammad (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This research investigates English as a Foreign Language (EFL) teachers’ perceptions of the implementation of Project-Based Learning (PjBL) in teaching seventh-grade students at SMPN 29 Pontianak and SMPN 3 Batu Ampar. The study aims to explore how teachers perceive, understand, and evaluate the effectiveness of PjBL in fostering meaningful learning, student engagement, and the development of 21st-century skills. Employing a qualitative descriptive approach, data were collected through interviews and documentation to gain in-depth insights into teachers’ experiences and perspectives. The findings reveal that teachers generally perceive PjBL positively as it provides opportunities for students to collaborate, communicate, and apply their language skills in authentic contexts. However, challenges such as limited time allocation, unequal student participation, and the need for careful planning were also highlighted. Despite these challenges, teachers acknowledged that PjBL enhances student motivation and encourages active learning. The study concludes that while PjBL requires adaptation and adequate support to be effectively implemented, it holds significant potential in improving students’ language skills and fostering holistic learning experiences. This research contributes to the understanding of how EFL teachers view PjBL in the Indonesian context and offers implications for improving teaching practices in secondary schools.